One thousand and one nights of tango: Moving between Argentina, North Africa, and the Middle East. Issue 1 (2nd January 2020) - Bennett, Kirsty
ABSTRACT: The Middle East and North Africa (MENA) rarely appear in any analysis of the global diffusion of Argentine tango. Yet, writers, musicians, singers, and dancers from the MENA region have long contributed to and drawn from tango as a cultural phenomenon in complex and multi-layered ways, as this essay demonstrates through a select taxonomy of historical, literary, musical, and dance encounters that culminates with a cross-cultural dialogue between Borges' analysis of the One Thousand and One Nights and the theology of Sufism in order to theorise the ineffable experience of the dance and the profundity of its music and lyric dimensions. Through a contrapuntal methodology that draws on my dual experience as a tango dancer and DJ, and as a literary and cultural historian of the MENA region, I explore these encounters and entanglements as opening new embodied pathways for South-South solidarity engendered through transnational "translations" of music and dance.